Entrepreneurship Development Trends in Perm and Sverdlovsk Region - RUDENKO, Marina N. (Journal of Advanced Research in Law and Economics; Vol 11 No 3 (2020): JARLE Volume XI Issue 3(49) Summer 2020DO - 10.14505/jarle.v11.3(49).35, 2020)
Increasing the level of entrepreneurial activity is determined by the extent to which its development is necessary to form a sustainable functioning of the region or the country as a whole. The relevance of the study is determined by the fact that the formation of entrepreneurial activity at the moment occurs only where there is a basis for social interaction between the subjects of entrepreneurship and society. The novelty of the study is determined by the fact that the paper uses a cluster approach, which allows to distinguish level estimates of the conditions of development of entrepreneurial activity. The author shows that the conditions for social interaction are the driver for development in the conditions of increasing the level of individualisation of social interaction. The article shows that social conditions determine the development of a new form of standardisation of entrepreneurship in the form of social entrepreneurship. The author demonstrates the mechanism of development of social entrepreneurship and the possibilities of its implementation both in the conditions of the innovative market and in the structure of stagnant market tendencies. The practical significance of the study is that social entrepreneurship is determined by the need to differentiate the conditions of its development and when forming cross-border clusters allows to predict and implement regional programs for the development of entrepreneurial activity.